2019
DOI: 10.1080/23802359.2019.1643801
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and analysis of the complete mitochondrial genome of Coenobita brevimanus

Abstract: Coenobitidae is one of the most important families in Anomura. However, systematic classification and taxonomic studies are still limited. In this study, we determined the complete mitochondrial genome (mitogenome) of Coenobita brevimanus and further explored the phylogenetic relationships of Anomura. In the whole mitogenome of C. brevimanus (16388 bp), the AT-skew is negative and the GC-skew is positive.The phylogenetic tree was constructed using MrBayes method ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Anomura was divided into two main branches in our phylogenetic tree, which was identi ed with the previous researches [35,51] Consistent with the traditional morphological classi cation, the phylogenetic analyses based on molecular methods showed that D. Edwardsii was clustered rstly clustered with the Diogenidae species Clibanarius infraspinatus and then clustered with another Diogenidae species Dardanus arrosor. As reported, Clibanarius infraspinatus possesses a favor of codon TAT(Ser) and owns a highest Ser content in amino acid composition [40], which showed the same pattern with D. Edwardsii.…”
Section: Phylogenetic Relationshipssupporting
confidence: 82%
See 1 more Smart Citation
“…Anomura was divided into two main branches in our phylogenetic tree, which was identi ed with the previous researches [35,51] Consistent with the traditional morphological classi cation, the phylogenetic analyses based on molecular methods showed that D. Edwardsii was clustered rstly clustered with the Diogenidae species Clibanarius infraspinatus and then clustered with another Diogenidae species Dardanus arrosor. As reported, Clibanarius infraspinatus possesses a favor of codon TAT(Ser) and owns a highest Ser content in amino acid composition [40], which showed the same pattern with D. Edwardsii.…”
Section: Phylogenetic Relationshipssupporting
confidence: 82%
“…For the D. Edwardsii mitogenome, the AT skew is -0.110, and the GC skew is 0.233, which indicates bias toward T and G. This asymmetry often occurs on Anomura species [11,[33][34][35]. In mammals, the duration of single-stranded state of the "heavy-stranded" genes during mitochondrial DNA replication can explain this asymmetry [36].…”
Section: Edwardsii Mitogenome Organizationmentioning
confidence: 99%
“…Notably, it substantially improves patient survival rates and overall outcomes. Concurrent lapatinib administration in clinical trials has consistently resulted in substantially prolonged survival without progression and overall survival incidences than separate agents for chemotherapy [15]. It highlights lapatinib's significance in such treatment.…”
Section: Applications Of Lapatinib In Breast Cancer Treatmentmentioning
confidence: 93%
“…Additional references were cited within the Supporting Information. [24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Supporting Informationmentioning
confidence: 99%
“…[20][21][22] Based on recent reports describing the utilization of (S(e)CN) 2 for electrophilic S(e)CN-transfer reactions, [20,21] we thus rationalize that these species are formed in situ under our reaction conditions and that they are acting as the relevant electrophilic S(e)CN-transfer reagents with different pronucleophiles. To substantiate this proposal, we synthesized selenocyanogen ((SeCN) 2 ) using a slightly adopted literature procedure 24 and reacted it with 1 a, which delivered product 3 a in comparable yield to our oxidative procedure (Scheme 2). Furthermore, MS analyses of mixtures of KSeCN or NaSCN and DBPO revealed the in situ formation of S(e)(CN) 2 and (S(e)CN) 2 (analogous NMR experiments did not allow us to detect these species directly but we only observed benzoic acid, which a) underscores the rapid reaction between DBPO and the used nucleophilic S(e)CN salts and b) the high reactivity and sensitivity of the hereby formed electrophilic species).…”
mentioning
confidence: 98%